Health of the War Worker (London : Labour Research Department)
1942-04 1942 1940s 44 pages employer to pay a lump sum. Such lump sums as are paid are sums which are agreed to be paid to get rid of the liability to make the weekly payments, but there is no procedure open to a workman compel an employer to pay a lump sum. The weekly payment before the war depended on the amount of the average weekly earnings with a maximum of 30/-. Since 1940 all workmen (married or single) drawing weekly compensation for total incapacity are entitled to an extra 5/- and (for male workmen only) an addition of 4/- per week for each of the first two children and 3/- for each subsequent child (whether dependent or not) up to a total of not more than ⅞ of the average weekly earnings. Partial incapacity depends upon the earning capacity of the injured workman. The Acts apply to many industrial diseases, a list of which can be obtained from the Factory Inspector. A workman can only compel payment of compensation for one of these diseases if he obtains from the Certifying Surgeon for the district in which he is last employed a certificate that he is suffering from the disease. This certificate is on a blue form and costs 5/-. If the doctor gives a certificate that he is not satisfied that the workman is suffering from the disease that also will cost 5/-. Either the workman or employers can appeal against the certificate within ten days but this is rather a complicated procedure. The certificate is the workman's property and should not be given to the employer. The workman should take the certificate to his Trade Union at once. If a workman is of opinion that any incapacity, injury, or disease is due to his employer's neglect or is due to a breach of any of the provisions of the Factories Act and regulations he should not accept any payments under the Workmen's Compensation Acts or he will bar a claim for damages based on the employer's negligence. In such a claim can be included loss of wages, pain and suffering, hospital and other expenses and disablement, exactly in the same way as in a claim by a man injured on the highway by the carelessness of a motorist. The workman should understand that the legal provisions for compensation and damages for accident are for the workman to utilize. No workman ought to get less money than he is entitled to. Trade Union officials and Shop Stewards can give assistance in these matters by mastering at any rate certain of the elementary technicalities about the injured workman's legal rights. The Trade Unionist will not, of course, be satisfied by seeing that the workman gets his legal rights. He will want to have these 22 21/2049